MEDIATISASI AGAMA DALAM FENOMENA DIMAS KANJENGTAAT PRIBADI SERTA KERJA LOGIKA MEDIA DALAM MEMBENTUK PENGETAHUAN PUBLIK SEBAGAI BAGIAN DARI AGEN SOSIAL DAN PERUBAHAN KULTURAL - Putri, Risky Chairani (Capture : Jurnal Seni Media Rekam, 2016)
The phenomenon,Dimas KanjengTaat Pribadi, is unique issues that have shocked in the Indonesian public because of his unbelievable activities (duplicate the amount of money).This metode of the research is textual;focus onTaat Pribadi news,doubling the money with the religion modus. Mediatisation theory explains about howTaat Pribadi work from the mediatisation, what things appear from the religion ,ediatisation , and how the logic of media work in this case (form knowledge) to the public.The findings of this study are mediatisation religion led to new understanding of the public that led to the substitution of the role of religion and peeps quast-religious.The logic of the media make the knowledge from public that the reporting on this case a shift is no longer focused on the case of deception,but tend to focus on the dramatization of the media or in other words experiencing commoditization of media content,as well as the logicof the media creating a privateTaat Pribadi as a new celebrity.Keywords: Mediatization, religion, logic media, commodification, and dramatization media